Why is your patient sedated?. Issue 4 (6th May 2014) - Murphy, Olwen; King, Graham; Callanan, Ian; W. Butler, Marcus
Abstract : Purpose: – The purpose of this paper is to examine the recording of clinical indication for prescribed sedative/hypnotic (SH) medications in a large, acute tertiary referral hospital. Design/methodology/approach: – All hospital inpatients' medications ( n =367) were audited for prescription details regarding SH medications. Medical notes were then examined for evidence of a recorded indication for such medications. Findings: – SH medications were prescribed to many hospital inpatients (42.5 per cent) during admission. An indication was documented in the nursing or medical records for 24.4 per cent of patients who were prescribed such medications. Nurses rather than by doctors prescribed most SH medications (74 vs 26 per cent, respectively, p =0.003). Some patients receiving SH medications were both over 65 and impaired in their mobility (19.2 per cent). The treatment indication was documented in 47 per cent. Practical implications: – Most patients prescribed SH medications have nothing in their medical record explaining why these drugs are being used, including half of the elderly, less mobile patients. All health professionals dealing with SH medications and doctors in particular need to justify the use of such medications in the medical record. For the particularly high-risk groups where SH medications are potentially more dangerous, explicit guidance on why and how such medications are to be used must be provided by prescribers. Originality/value: – For the first time, data are presented on documentation rates for clinical indication of prescribed SH medications across a large acute hospital, and highlights significant shortcomings in practice. This study should inform other organisations of the need to be mindful of facilitating greater compliance with good prescribing practice.